Candidate Heterotaxy Gene FGFR4 Is Essential for Patterning of the Left-Right Organizer in Xenopus - Sempou, Emily; Lakhani, Osaamah Ali; Amalraj, Sarah; Khokha, Mustafa K. (Frontiers in Physiology, 2018)
Congenital heart disease (CHD) is the most common birth defect, yet its genetic causes continue to be obscure. Fibroblast growth factor receptor 4 (FGFR4) recently emerged in a large patient exome sequencing study as a candidate disease gene for CHD and specifically heterotaxy. In heterotaxy, patterning of the left-right (LR) body axis is compromised, frequently leading to defects in the heart's LR architecture and severe CHD. FGF ligands like FGF8 and FGF4 have been previously implicated in LR development with roles ranging from formation of the laterality organ [LR organizer (LRO)] to the transfer of asymmetry from the embryonic midline to the lateral plate mesoderm (LPM). However, much less is known about which FGF receptors (FGFRs) play a role in laterality. Here, we show that the candidate heterotaxy gene FGFR4 is essential for proper organ situs in Xenopus and that frogs depleted of fgfr4 display inverted cardiac and gut looping. Fgfr4 knockdown causes mispatterning of the LRO even before cilia on its surface initiate symmetry-breaking fluid flow, indicating a role in the earliest stages of LR development. Specifically, fgfr4 acts during gastrulation to pattern the paraxial mesoderm, which gives rise to the lateral pre-somitic portion of the LRO. Upon fgfr4 knockdown, the paraxial mesoderm is mispatterned in the gastrula and LRO, and crucial genes for symmetry breakage, like coco, xnr1, and gdf3 are subsequently absent from the lateral portions of the organizer. In summary, our data indicate that FGF signaling in mesodermal LRO progenitors defines cell fates essential for subsequent LR patterning.